An approach to separation efficiency modelling of structured packings based on X-ray tomography measurements: Application to aqueous viscous systems. (31st August 2019) - Große Daldrup, A.; Crine, M.; Marchot, P.; Toye, D.; Kenig, E.Y.
Highlights: Experimental study and modelling of flow and mass transfer in structured packings. Qualitative and quantitative results obtained by XCT image analysis. Separation efficiency model for aqueous viscous systems in structured packings. Separation efficiency measurements of CO2 -desorption from glycerin-water mixtures. Rising liquid viscosity leads to a significant decrease in separation efficiency. Abstract: The objective of this work is the development of a model to predict the separation efficiency of structured packings for aqueous viscous systems. The modelling approach is based on a hydrodynamic analogy between the real complex flow patterns and simplified fluid dynamic elements. Understanding of dominating liquid flow patterns inside structured packing is essential for the model development. Therefore, in this work, X-ray tomography is used to investigate liquid flow morphology. To study the influence of viscosity, water and water/glycerine mixtures are employed as working liquids. X-ray tomography permits the spatial distribution of liquid in the cross-section of a column filled with MellapakPlus 752.Y packing elements to be determined. The resulting images are used to evaluate liquid hold-up and gas-liquid interfacial area. Furthermore, liquid flow patterns (film flow, contact-point liquid, flooded regions) are identified, and their contribution to the overall hold-up is determined in dependence on flow rate and liquid viscosity. The results of the liquid flow morphology analysis help to develop a hydrodynamic analogy model. To implement the gas-liquid contact area and the flooded regions into this model, the packing is represented as a bundle of dry, filled and irrigated cylindrical channels, while the ratio between different channel types is determined from the analysis of tomographic images. This simplified hydrodynamic description allows a direct application of rigorous partial differential transport equations, and their solution yields local concentration fields which are used for the evaluation of the separation efficiency. The new modelling approach is validated by comparison with separation efficiency data obtained from experiments with CO2 desorption from saturated water-glycerine mixtures into air.